2007
DOI: 10.1007/bf03030663
|View full text |Cite
|
Sign up to set email alerts
|

Coastal plant and soil relationships along the southwestern coast of South Korea

Abstract: We studied how plant species distribution was regulated by the relationships between vegetation and soil factors on the southwestern coast of South Korea. Vegetation was classified using two-way indicator species analysis (TWINSPAN), thereby producing four vegetation groups that were linked to three habitat types. Two ordination techniques --detrended correspondence analysis (DCA) and canonical correspondence analysis (CCA) --were applied to examine the relationships between vegetation and 12 edaphic factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
(20 reference statements)
2
20
0
1
Order By: Relevance
“…Sand dune species group (group 3) showed association with Carex kobomugi, Messerschmidia sibirica, Carex pumila, E. mollis, Ischaemum anthephoroides, Ixeris repens, Lysimachia mauritiana, Salsola komarovi, and Vitex rotundifolia. After examining environmental correlates of species distribution within these three habitat types using DCA and CCA ordination results of coastal plant data set, Ihm et al (2007) have shown similar ordination results.…”
Section: Habitat Characteristics and Soil Factorsmentioning
confidence: 77%
See 2 more Smart Citations
“…Sand dune species group (group 3) showed association with Carex kobomugi, Messerschmidia sibirica, Carex pumila, E. mollis, Ischaemum anthephoroides, Ixeris repens, Lysimachia mauritiana, Salsola komarovi, and Vitex rotundifolia. After examining environmental correlates of species distribution within these three habitat types using DCA and CCA ordination results of coastal plant data set, Ihm et al (2007) have shown similar ordination results.…”
Section: Habitat Characteristics and Soil Factorsmentioning
confidence: 77%
“…The development of estuary marsh is related to sedimentation in rivers and tides (Viles and Spencer 1995;Park 2000;Oh and Bang 2003). Halophyte distribution patterns can change according to the development of sedimentation geomorphology and soil texture (Lee 2011;Ihm et al 2007) as well as time duration of tidal flooding (Park 2008). Outer physical influence can also affect salt marsh sediment (Hong 2000;Korea Environment Institute 2006).…”
Section: Habitat Characteristics and Soil Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…At very high soil elevations, above mean high sea level (MHSL), soil salinity tends to decrease because of less frequent flooding and associated reduced salt input (Phleger 1971;Mahall and Park;Sánchez et al 1996;Ihm and Lee 1998;Rogel et al 2000;2001;Pennings et al 2005;Silvestri et al 2005;Ihm et al 2007;Angiolini et al 2013;Cho 2015). This observation, which provides a link between the presence of halophytes and topographic elevation, may be explained by noting that evaporation periods (occurring when the marsh is not flooded) are longer at higher elevations and, thus, salts in surface soils may become very concentrated.…”
Section: Otic Factorsmentioning
confidence: 99%
“…Numerous studies have reported relationships between coastal plant communities and moisture content of the soil (Omer 2004;Ihm et al 2007;Lee et al 2007;González-Alcaraz et al 2014). The distribution of plant species responds to changes in soil moisture and, hence, monitoring of vegetation has been proposed as an effective tool to detect important species in wetlands (Hong 2015).…”
Section: Otic Factorsmentioning
confidence: 99%